2017
DOI: 10.1016/j.hpb.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic preconditioning in orthotopic liver transplantation (RIPCOLT trial): a pilot randomized controlled feasibility study

Abstract: Abstract:Ischaemia Reperfusion (IR) injury is a major cause of post-operative morbidity, mortality and graft loss following Orthotopic Liver Trasnplantation (OLT). There is no current accepted treatment for IR injury. The recent drive to implant more marginal grafts, which are more susceptible to IR injury makes this clinical problem a key research goal. Remote Ischaemic Preconditioning (RIPC) has been shown to ameliorate hepatic IR injury in small animal models. Whether recipient RIPC can reduce IR injury in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 46 publications
3
35
0
Order By: Relevance
“…RIPC is a recent preconditioning method, and its clinical efficacy is being evaluated. 21,22 We have initiated a clinical trial assessing the impact of RIPC on postoperative complications associated with major surgical procedures including hepatectomies (NCT02375269). Meanwhile, experimental data can give hints to estimate the advantages that may be expected from RIPC.…”
Section: Discussionmentioning
confidence: 99%
“…RIPC is a recent preconditioning method, and its clinical efficacy is being evaluated. 21,22 We have initiated a clinical trial assessing the impact of RIPC on postoperative complications associated with major surgical procedures including hepatectomies (NCT02375269). Meanwhile, experimental data can give hints to estimate the advantages that may be expected from RIPC.…”
Section: Discussionmentioning
confidence: 99%
“…For RIPC, the most widely used technique is clamping one limb of a patient 25 or animal. 26 However, for our project we chose a different target territory, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…26 On the other hand, our results are consistent with those from human studies in which direct and remote IPC increased AST and ALT values 24h after reperfusion. 25,30 We made a refinement in this current investigation, by adding some molecular analyses that could show some beneficial effects of IPC. In the liver tissue, the combined IPC approach resulted in marked positive changes in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…This was repeated twice and completed prior to the transplant procedure. Authors demonstrated that RIPC is feasible, acceptable to patients and safe in this group of patients but clinical benefits within the first 3 months post transplantation were not detected [75]. Authors suggest that 5 min cycles are insufficient to create localized ischemia in the limb [75].…”
Section: Ripc In Orthotopic Liver Transplantationmentioning
confidence: 97%
“…The first trial to investigate the feasibility of RIPC in liver transplant recipients was addressing by Robertson et al [75]. The trial involved randomization of adult recipients undergoing deceased donor liver transplantation.…”
Section: Ripc In Orthotopic Liver Transplantationmentioning
confidence: 99%